POLA DISTRIBUSI PASIEN KANKER KOLOREKTAL DI RUANG RAWAT INAP RSU DR. SOEDARSO PONTIANAK TAHUN 2007-2011 - ., Wina Winanda (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background. Colorectal cancer is a cancer that found in the colon or rectum. The incidence of colorectal cancer increases with age especially after 45 age. The incidence and mortality of this cancer is ten of the most common cancer.Objective. This research was aimed to know the distribution of colorectal cancer patients according to main symptoms, pathologic stage, and treatment from hospital in care units of RSU dr. Soedarso on 2007-2011.Method. This research was a descriptive study with cross-sectional approach which was conducted by using secondary data from medical records.Result. Among a total of 64 colorectal cancer patients, the most common main symptom is blood stool with 18 patients (28,12%)) and followed by obstipation with 17 patients (26,12%). Amount of 37 patients (57,81%) came with stage Dukes C and 4 patients (6,25%) with stage Dukes D. The most common treatment was chemotherapy with 27 patients (42,12%).Conclusion. The most common main symptom of patients with colorectal cancer have hospitalization in RSU dr. Soedarsol is blood stool. The most common pathologic stage is stage Dukes C. The most common treatment is chemotherapy.Keyword: colorectal cancer, main symptom, pathologic stage, treatment